2013
DOI: 10.1039/c3sc50496d
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier trapping, recombination and transfer in hematite (α-Fe2O3) water splitting photoanodes

Abstract: Hematite is currently considered one of the most promising materials for the conversion and storage of solar energy via the photoelectrolysis of water. Whilst there has been extensive research and much progress in the development of hematite structures with enhanced photoelectrochemical (PEC) activity, relatively limited information has been available until recently concerning the dynamics of photogenerated charge carriers in hematite and their impact upon the efficiency of water photoelectrolysis. In this per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

50
482
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 435 publications
(535 citation statements)
references
References 96 publications
50
482
2
Order By: Relevance
“…Our studies thus demonstrate that internal fi elds can indeed result in a spatial separation of charge carriers, and thereby a reduction in charge recombination losses, potentially enhancing solar conversion device performance. For example, the lifetimes observed here match the rate constants of photoelectrochemical water oxidation reported in the literature, [ 25,43 ] indicating that ferroelectrics could have a particularly high impact in solar water splitting systems. Further, we have previously shown that even an order of magnitude increase carrier lifetime can result in 100 mV increase in ) there is no polarization and thus no band bending (for clarity, band bending due to atmospheric effects is omitted here, although it is likely that some upward band bending exists above T C ).…”
Section: Doi: 101002/adma201601238supporting
confidence: 85%
See 4 more Smart Citations
“…Our studies thus demonstrate that internal fi elds can indeed result in a spatial separation of charge carriers, and thereby a reduction in charge recombination losses, potentially enhancing solar conversion device performance. For example, the lifetimes observed here match the rate constants of photoelectrochemical water oxidation reported in the literature, [ 25,43 ] indicating that ferroelectrics could have a particularly high impact in solar water splitting systems. Further, we have previously shown that even an order of magnitude increase carrier lifetime can result in 100 mV increase in ) there is no polarization and thus no band bending (for clarity, band bending due to atmospheric effects is omitted here, although it is likely that some upward band bending exists above T C ).…”
Section: Doi: 101002/adma201601238supporting
confidence: 85%
“…[ 25 ] We also note that the absence of a further sharp reduction in carrier lifetime as the temperature is increased above T C is most probably due to charge trapping effects becoming the dominant limitation on charge carrier recombination on these timescales, as has been reported for other metal oxides.…”
Section: Doi: 101002/adma201601238supporting
confidence: 69%
See 3 more Smart Citations